Ryparkens venner - Thing, Morten (Arbejderhistorie, 2012)
Morten Thing: The Friends of Ry Park. Opposition to the inadequate judicial reckoning after the end of the war, Arbejderhistorie 3/2012, pp. 95-108. From January 1946 to February 1947 Copenhageners were witnesses to a series of illegal actions, which were focused on drawing attention to the slowness in bringing collaborators with the Germans during the occupation to account. The group, ‘The Friends of Ry Park`, was responsible to a large extent for the actions. Ry Park was the place where the Germans executed members of the resistance. Among others, the group was composed of former resistance fighters who were armed. On the basis of legal documents/papers a history is uncovered and told, which has previously not left a mark in the literature on the occupation.